The bacterial pathogen Listeria monocytogenes: an amazing multifaceted model - Cossart, Pascale (Henry Stewart Talks, 2009)
Host-pathogen interactions, Successive steps of human listeriosis, Listeriosis: a model of infection, Listeria monocytogenes : the rise of a multifaceted model, Entry into non-phagocytic cells, The cell infection process, The Listeria monocytogenes virulence gene regulon, Bacterial-induced phagocytosis, The inlAB operon, Internalin, E-cadherin, ARHGAP10, Interaction between Internalin and E-cadherin, The InlB signaling pathway, Endocytosis and degradation of RTKs, Model: exploitation of the endocytosis machinery for invasion of mammalian cells, Clathrin, Is the mechanism used by Listeria a rule rather than an exception?, What is the role of InlB in vivo?, Epidemiological survey, InlA and InlB play interdependent roles during feto-placental listeriosis, Roles of InlA and InlB in infection, Comparative genomics, Histone modifications, Epigenetics and bacterial infectious diseases, Contribution of the Listeria model to biology